A Note on Religion. (October 2021) - Betzig, Laura
At the beginning of our era, after a battle on the Ionian Sea, Antony and Cleopatra took their own lives in Egypt, and Augustus was made an imperator by his senators . Roman emperors had sexual access to those senators' daughters and wives, and to thousands of slaves. But they ran governments with help from their cubicularii, castrated civil servants. And they enforced an Imperial Cult: subjects made sacrifices to the emperor's genius, or procreative spirit; or they got disemboweled by wild animals, or decapitated. Then Constantine moved off from the Tiber to the Bosporus, and Europe was ruled over by a few. Lords covered the countryside with bastards, but passed on estates on to their oldest sons. Daughters and younger sons were put away in the Church, where some became parents, but most were reproductively suppressed: they were ἄνανδρος or anandros, or without a husband, and ἄγαμος or agamos, or without a wife. Heretics who objected got burned at the stake. Then the Crusaders expanded Europe to the East, and Columbus went off to the West, and politics, sex and religion became more democratic. Power was more widely distributed; more men and women had families if they wanted them, and monasteries emptied out. The Reformation followed the Roman Church, which had followed the Imperial Cult.